Multifocal arteriovenous malformation of face: A rare entity - Gouthami Karankot; Rashmitha Arutla; Ritesh Rajan; Sharath Reddy (Wolters Kluwer Medknow Publications, 2020)
Vascular anomalies are a heterogeneous group of congenital disorders with abnormal vascular development. Vascular anomalies are classified into vascular tumors and malformations. Vascular malformations are resulted from abnormal vessel development and morphogenesis. Arteriovenous malformation (AVM) of the head and neck accounts to 0.1%, which is persistent, progressive in nature and might represent a lethal benign disease. Here, we present a case report of a 32-year-old female with AVM involving the left side of the face.